The telomerase inhibitor imetelstat differentially targets JAK2V617F versus CALR mutant myeloproliferative neoplasm cells and inhibits JAK-STAT signaling - Olschok, Kathrin; Altenburg, Bianca; de Toledo, Marcelo A. S.; Maurer, Angela; Abels, Anne; Beier, Fabian; Gezer, Deniz; Isfort, Susanne; Paeschke, Katrin; Brümmendorf, Tim H.; Zenke, Martin; Chatain, Nicolas; et al. (Frontiers in Oncology, 2023)
Imetelstat shows activity in patients with myeloproliferative neoplasms, including primary myelofibrosis (PMF) and essential thrombocythemia. Here, we describe a case of prolonged disease stabilization by imetelstat treatment of a high-risk PMF patient enrolled into the clinical study MYF2001. We confirmed continuous shortening of telomere length (TL) by imetelstat treatment but observed emergence and expansion of a KRAST58I mutated clone during the patient’s clinical course. In order to investigate the molecular mechanisms involved in the imetelstat treatment response, we generated induced pluripotent stem cells (iPSC) from this patient. TL of iPSC-derived hematopoietic stem and progenitor cells, which was increased after reprogramming, was reduced upon imetelstat treatment for 14 days. However, while imetelstat reduced clonogenic growth of the patient’s primary CD34+ cells, clonogenic growth of iPSC-derived CD34+ cells was not affected, suggesting that TL was not critically short in these cells. Also, the propensity of iPSC differentiation toward megakaryocytes and granulocytes was not altered. Using human TF-1MPL and murine 32DMPL cell lines stably expressing JAK2V617F or CALRdel52, imetelstat-induced reduction of viability was significantly more pronounced in CALRdel52 than in JAK2V617F cells. This was associated with an immediate downregulation of JAK2 phosphorylation and downstream signaling as well as a reduction of hTERT and STAT3 mRNA expression. Hence, our data demonstrate that imetelstat reduces TL and targets JAK/STAT signaling, particularly in CALR-mutated cells. Although the exact patient subpopulation who will benefit most from imetelstat needs to be defined, our data propose that CALR-mutated clones are highly vulnerable.